2019
DOI: 10.1371/journal.pone.0225725
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and associated factors among type-2 diabetes mellitus patients attending public hospitals in Harari Region, Eastern Ethiopia

Abstract: BackgroundAnemia is a common complication of diabetes mellitus, therefore having a major impact on the overall health and survival of diabetic patients. However, there is a paucity of evidence of anemia among diabetic patients in Ethiopia, particularly in Harari Region. Therefore, this study aimed to assess the magnitude of anemia and associated factors among Type 2 Diabetes Mellitus (T2DM) patients attending public hospitals in Harari Region, Eastern Ethiopia.MethodsA hospital based cross-sectional study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
32
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 30 publications
11
32
5
Order By: Relevance
“…Anaemia is more likely to occur in male patients compared to female patients. Similar finding have been reported in Ethiopia [ 13 ]. However, this finding was contraindicating with another study performed in Pakistan [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Anaemia is more likely to occur in male patients compared to female patients. Similar finding have been reported in Ethiopia [ 13 ]. However, this finding was contraindicating with another study performed in Pakistan [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…The current study demonstrated the prevalence of anaemia among T2DM patients in UOGCSH to be 8.06%. This number is lower than the finding of a hospital-based cross-sectional study performed in Harari region, Eastern Ethiopia (34.8%), and northeast of the country (20.1%) [ 13 , 16 ]; this prevalence is also lower than previous studies in Iran (30.4%), India (18%), and Malaysia (39.4%) [ 17 – 19 ]. Such variations in the magnitude of anaemia among diabetic patients might be due to differences in the cutoff value used to measure it, sample size, and variations in the overall characteristics of the study area that could be related to the prevalence of anaemia among T2DM patients.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…patients. The minimum and maximum prevalence of anaemia were 8.06% and 34.8% in Gondar23 and Harari,27 respectively. The overall pooled prevalence of anaemia in DM patients using the random ef-Descriptive summary of 9 included studies on the prevalence of anaemia in DM patients in Ethiopia = 86.7% and 26.34% (95% CI: 9.77-42.90) I 2 = 95.9%, respectively.…”
mentioning
confidence: 92%